Lean, green and clean? Sustainability reporting in the logistics sector - Wim Lambrechts; Semen Son-Turan; Lucinda Reis; Janjaap Semeijn (Logistics, 2019)
Transport and logistics activities contribute heavily to global sustainability problems, yet the implementation of corporate social responsibility and sustainability reporting in the sector lags behind. This paper aims to analyze sustainability reporting in the logistics sector, with focus on environmental, social and economic indicators. An extensive operationalization of sustainability indicators is used to examine and analyze the sustainability reports of 52 organizations in the logistics sector worldwide. Results show that the sector does not agree on the materiality of sustainability indicators. Furthermore, sustainability reporting seems to be incompatible with daily operations, leading to obscurity in reports. This contrast, between the necessary existence of organizations in the logistics sector and their undesirable environmental and social effects, calls for future research into how organizations are coping with this paradox. A viable way forward is needed in order to ensure materiality in the sectors' efforts toward sustainability reporting.
Keywords: 650; Global Reporting Initiative (GRI); legitimacy theory; logistics sector; materiality; stakeholder theory; sustainability disclosure; sustainability indicators